Antibiotic resistance and biosafety of Vibrio cholerae and Vibrio parahaemolyticus from freshwater fish at retail level - Ahmad, Noorlis; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Radu, Son; Tuan Chilek, Tuan Zainazor; Wong, Woan Chwen; Robin, Tunung; Pui, Chai Fung; Nishibuchi, Mitsuaki; Nakaguchi, Yoshitsugu (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
A total of 49 isolates of V. parahaemolyticus and 8 isolates of V. cholerae isolated from freshwater fish of patin (Pangasius hypopthalmus) and red tilapia (Oreochromis sp.) were purchased from different retail level in Selangor, Malaysia. All of the isolates showed a multiple resistances towards all 15 antibiotics tested. Some of the isolates show a high resistance to different antibiotics including bacitracin, vancomycin, tetracycline, furazididone, cephalothin and erythromycin. However, both species was susceptible towards imipenem. Overall antibiotics resistance patterns of all isolates were resistant from 2 to 14 resistance patterns with multiple antibiotic resistance (MAR) index ranging from 0.13 to 0.93 respectively. As the results obtained in the dendrogram produced from both species had indicates that these antibiotics were intensively used whether in the aquaculture farm through feeds during culture or at the hatchery production of seed. Thus, this study will provides an essential information of the MAR index and also the clustering analysis in order to determine the biosafety of Vibrio spp. in freshwater aquaculture fish sold at different retail level in Malaysia.